Effectiveness of Adlerian Therapy and Satir’s Model in the ‎Treatment of Obsessive-Compulsive Disorder in a Sample ‎of Female Syrian Refugees - Alquran, Roa’a; Jaradat, Abdul-Kareem (Jordan Journal of Educational Sciences, 2020)
The present study aimed at investigating the effectiveness of a therapeutic program based on Adlerian Therapy, and on Satir’s Model in treating obsessive-compulsive disorder (OSD) among a sample of Syrian refugee female adolescents. The study population consisted of (158) students in grades (7-10), selected from a school in Irbid Governorate. In order to achieve the aims of this study, a modified version of the Maudsley Obsessional-Compulsive Inventory was used. The sample of the study consisted of (35) students, who scored the highest on the OCD Scale. These students were randomly assigned to three groups. two experimental groups and one control group. Each of the experimental groups consisted of (12) participants. Wherease the control group consisted of (11) participants, One of the experimental groups received Adlerian therapy, while the other received training on Satir’s Model. As for the control group, students in this group did not receive any treatment.Results showed that the Adlerian therapy was significantly more effective in reducing OCD than Satir’s Model and the no treatment group in the posttest, while Satir’s Model was significantly more effective in reducing OCD than the no treatment group in the posttest.